Euglycemic Diabetic Ketoacidosis in a Patient with Cocaine Intoxication - Asma Abu-Abed Abdin; Muhammad Hamza; Muhammad S. Khan; Awab Ahmed (Case Reports in Critical Care)
Diabetic ketoacidosis (DKA) is characterized by elevated anion gap metabolic acidosis, hyperglycemia, and elevated ketones in urine and blood. Hyperglycemia is a key component of DKA; however, a subset of DKA patients can present with near-normal blood glucose, an entity described as “euglycemic DKA.” This rare phenomenon is thought to be due to starvation and food restriction in insulin dependent diabetic patients. Cocaine abuse is considered a trigger for development of DKA. Cocaine also has anorexic effects. We describe an interesting case of euglycemic DKA in a middle-aged diabetic female presenting with elevated anion gap metabolic acidosis, with near-normal blood glucose, in the settings of noncompliance to insulin and cocaine abuse. We have postulated that cocaine abuse was implicated in the pathophysiology of euglycemic DKA in this case. This case highlights complex physiological interplay between type-1 diabetes, noncompliance to insulin, and cocaine abuse leading to DKA, with starvation physiology causing development of euglycemic DKA.